Clinical presentation of vernal keratoconjunctivitis in Bharatpur Medical College - Dahal, Polina; Bhattarai, Sanjeet (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: To evaluate the different clinical presentation of Vernal Keratoconjunctivitis (VKC) in our context. Materials & Methods: Ninety diagnosed VKC patients attending the outpatient department of College of Medical Sciences from 1st March 2014 to 1st June 2015 were enrolled in the study. Results: The study revealed male predominance (83.33%). Commonly occurring symptoms were itching (100%) and redness (80%). Commonest sign was tarsal papillae (100%). Conjunctival hyperemia was seen in 94.1% cases and 180 eyes of 90 cases showed Vernal Keratoconjunctivitis. Conclusion: The clinical presentation of VKC patients in our context are very much similar to the findings of the other study done in Nepal and other parts of the world. Commonly occurring symptoms are itching, redness and commonly occurring signs are tarsal papillae and conjunctival hyperemia. JCMS Nepal. 2015; 11(2):17-19